ESTIMASI BIAYA DAN WAKTU DALAM PROJECT PLAN PEMBUATAN WEBSITE DENGAN PENDEKATAN INFORMATION TECHONOLOGY (IT) PROJECT MANAGEMENT (Studi Kasus Pada Kecamatan Sebangau Kota Palangka Raya) (Universitas Palangka Raya, 2014)
The project is an activity that can be planned and implemented in a unified form using arange of resources to obtain profit. The project involves two parties work together to comply withthe agreed rules. The failure of a project is very common. This is due to the lack of propermanagement of the resources that must be managed. The failure of the project not only resulted inloss of time, but more fatal is the financial loss. The two parties involved in the project will beequally menanggun a result of the failure of the project. Subdistrict sebagau of duty and service tothe community and government, planning a website design project. In this plan, the districtsinvolving a consultant in planning, especially in the estimation of the cost and time required.This study projecting the need for cost and time views of the need for the scope of work /projects using Information Technology Project Management approach in the area of TimeManagement and Cost Management.From the research, in building a website District Office Sebangau Palangkaraya takes 8months with an estimated cost of Rp. 184 565 000, -